PENILAIAN KINERJA PELAYANAN ANTENATAL PADA PUSKESMAS ISO DAN PUSKESMAS TIDAK ISO DI KABUPATEN SLEM - , AMALINA TRI SUSILANI; , Prof. Djaswadi Dasuki, SpOG(K), MPH, PhD, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Quality antenatal care is a strategic basic medical service to maintain health and early detection of pregnancy disorders. The results of basic health research by the Public Health Research and Development in 2008 showed that pregnant women carrying out a complete examination were as many as 84.5% that should have been 100%. In Sleman, coverage of antenatal visits for V4 in 2009 declined and did not reach the target of national standards by 95% and the maternal mortality rate reached 5 persons and infant mortality reached 105 cases. Therefore, performance assessment, especially in health centers that have been standardized both ISO and non- ISO in Sleman, needs to be done. Objective: To determine the performance of antenatal care between health centers with ISO and health centers without ISO using the BSC. Method: This was an observational study with retrospective design. The study was conducted at two health centers, namely ISO Health Center (Ngaglik I) and non ISO Health Center (Turi). The selection of sites was based purposive sampling. Study sample was the Head of Health center, midwife coordinator and implementers in the MCH room and third trimester pregnant women. The data analysis was done by univariate, bivariate, and multivariate analyses. Results: Officersâ compliance in the service standards to the satisfaction of patients showed a significant relationship in Ngaglik I Health Center indicated with a correlation score of 0.65 with p value <0.05. The patientsâ loyalty in Ngaglik I Health Center was better than Turi Health Center (c 2 = 10.53, p = 0.001